2017
DOI: 10.1111/hepr.12886
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognostic factors of liver cirrhosis patients with systemic inflammatory response syndrome

Abstract: Cr ≥ 175 µmol/L, CRP ≥ 25 mg/L, multi-site infection, ACLF, and advanced HCC independently predicted a higher rate of 90-day mortality in liver cirrhosis with SIRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…It had been recognized that the severity of portal hypertension and circulatory dysfunction can lead to an increase in levels of biomarkers associated with systemic inflammation (such as WBC and interleukin [IL]‐6) and impaired intestinal integrity (FABP2), of which systemic inflammation may be a key driver of clinical deterioration 24 . Systemic inflammation in cirrhotic patients maximizes the risk of complications, such as VH, 25 hepatic encephalopathy, 26 and increased the mortality rate 27,28 . CRP, the production of which is stimulated by IL‐6 synthesis, is strongly associated with an ongoing systemic proinflammatory response, during which hepatic endothelial dysfunction elevates vasoconstrictor production, leading to deteriorated portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It had been recognized that the severity of portal hypertension and circulatory dysfunction can lead to an increase in levels of biomarkers associated with systemic inflammation (such as WBC and interleukin [IL]‐6) and impaired intestinal integrity (FABP2), of which systemic inflammation may be a key driver of clinical deterioration 24 . Systemic inflammation in cirrhotic patients maximizes the risk of complications, such as VH, 25 hepatic encephalopathy, 26 and increased the mortality rate 27,28 . CRP, the production of which is stimulated by IL‐6 synthesis, is strongly associated with an ongoing systemic proinflammatory response, during which hepatic endothelial dysfunction elevates vasoconstrictor production, leading to deteriorated portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 CRP, the production of which is stimulated by IL-6 synthesis, is strongly associated with an ongoing systemic proinflammatory response, during which hepatic endothelial dysfunction elevates vasoconstrictor production, leading to deteriorated portal hypertension. Turco et al29 demonstrated that CRP could be used to predict the clinical outcomes of both patients with compensated and decompensated cirrhosis.…”
mentioning
confidence: 99%
“…Creatinine ≥175 µmol/L, C-reactive protein (CRP) ≥25 mg/L, multisite infection, acute-on-chronic liver failure, and advanced hepatocellular carcinoma were also identified as independent predictors of 90-day mortality in cirrhotic patients with systemic inflammatory response syndrome (commonly known as SIRS). Similarly, another study also demonstrated that a procalcitonin level of ≥1.0 ng/mL can predict the 90-day mortality rate for liver cirrhosis, but only in univariate analysis 28…”
Section: Application Of Pct In Liver Diseasesmentioning
confidence: 95%
“…GALT constitutes the largest lymphoid organ of the body, and its activation in portal hypertensive enteropathy results in the release of several inflammatory mediators. These mediators would be transported by the intestinal lymph nodes to the pulmonary circulation inducing an inflammatory phenotype and later to the systemic circulation [91,118,119].…”
Section: The Reexpression Of the Trophoblastic-yolk Sac-related Phenomentioning
confidence: 99%